2013
DOI: 10.1097/aog.0b013e31827c5de7
|View full text |Cite
|
Sign up to set email alerts
|

Incontinence Outcomes in Women Undergoing Primary and Repeat Midurethral Sling Procedures

Abstract: Objective-To assess stress urinary incontinence (SUI) and other lower urinary tract symptom outcomes in women undergoing a repeat midurethral sling compared to those undergoing primary midurethral sling.Material and Methods-Cure was defined as responses of "not at all" or "somewhat" to both questions of the SUI subscale of the Urogenital Distress Inventory-6 (UDI-6); symptom impact was assessed using the Incontinence Impact Questionnaire-7. Multivariable models were created controlling for baseline Medical Epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 17 publications
3
24
0
Order By: Relevance
“…In the present study, the repeat MUS procedure was successful in 37 of 53 patients (69.8 %) with recurrent or persistent SUI with a mean follow-up of 54.6 months. Although it is difficult to compare the findings of studies because differences in the definitions of success or cure, our results are similar to those reported previously [9,[13][14][15][16]. The success rate in this study was higher than those of other minimally invasive treatments for persistent or recurrent SUI.…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…In the present study, the repeat MUS procedure was successful in 37 of 53 patients (69.8 %) with recurrent or persistent SUI with a mean follow-up of 54.6 months. Although it is difficult to compare the findings of studies because differences in the definitions of success or cure, our results are similar to those reported previously [9,[13][14][15][16]. The success rate in this study was higher than those of other minimally invasive treatments for persistent or recurrent SUI.…”
Section: Discussionsupporting
confidence: 78%
“…Lee et al reported that a repeat MUS procedure had a cure rate of 75.9 % in 29 patients with failure of the initial procedure after a mean follow-up of 18.1 months [13]. Stav et al [14] and Parden et al [16] also found overall subjective cure rates following repeat MUS procedures of 62 % and 54 % with mean follow-up periods of 50 and 38 months, respectively. Another retrospective study in 80 patients showed subjective and objective cure rates following MUS procedures of 61.0 % and 63.5 %, respectively, with a mean follow-up of 44.8 months [15].…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations